PHYTOREMEDIATION ROLE IN INCREASING RICE (Oryza Sativa L.) PRODUCTION WITH REDUCED MERCURY CONTENT IN MERCURY CONTAMINATED SOIL - M. Syahril,; Rosmayati,; N. Rahmawati, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This study aimed to obtain phytoremediator that have better effectiveness to accumulating mercury so as to reduce mercury content in grains, research was conducted on mercury-contaminated rice fields. The study was conducted withim randomized block design with 3 replications.  First factors are varieties namely Ciherang, IR-64, Siganteng (local variety), and Inpari-32, the second are the type of phytoremediator, namely: Kiambang, Eceng Gondok and Jerango and  third factor are population of phytoremediator, namely: without phytoremediator, 5, 10 and 15 plants per plot. The plot size used was 1 metre x 2 meters with 20 rice plants per plot.  The results showed that there was a decrease in mercury content in rice grains of all varieties below the quality standard threshold in eceng gondok and jerango treatments with population 10 and 15 plants per plot. The results obtained to reduce the mercury content below the quality standard threshold with high production can be done by the application of jerango phytoremediators with population 10 plants per plot with the best variety is IR-64.